Repeated exposure of nosocomial pathogens to silver does not select for silver resistance but does impact ciprofloxacin susceptibility. (15th October 2021) - Villapún, Victor M.; Balacco, Dario L.; Webber, Mark A.; Hall, Thomas; Lowther, Morgan; Addison, Owen; Kuehne, Sarah A.; Grover, Liam M.; Cox, Sophie C.
Abstract: The rise of antimicrobial resistant bacteria coupled with a void in antibiotic development marks Antimicrobial Resistance as one of the biggest current threats to modern medicine. Antimicrobial metals are being developed and used as alternative anti-infectives, however, the existence of known resistance mechanisms and limited data regarding bacterial responses to long-term metal exposure are barriers to widespread implementation. In this study, a panel of reference and clinical strains of major nosocomial pathogens were subjected to serial dosage cycles of silver and ciprofloxacin. Populations exposed to silver initially showed no change in sensitivity, however, increasingly susceptibility was observed after the 25th cycle. A control experiment with ciprofloxacin revealed a selection for resistance over time, with silver treated bacteria showing faster adaptation. Morphological analysis revealed filamentation in Gram negative species suggesting membrane perturbation, while sequencing of isolated strains identified mutations in numerous genes. These included those encoding for efflux systems, chemosensory systems, stress responses, biofilm formation and respiratory chain processes, although no consistent locus was identified that correlated with silver sensitivity. These results suggest that de novo silver resistance is hard to select in a range of nosocomial pathogens, although silver exposure may detrimentally impact sensitivity to antibiotics in the long term. Statement of significance: The adaptability of microbial life continuously calls for the development of novel antibiotic molecules, however, the cost and risk associated with their discovery have led to a drying up in the pipeline, causing antimicrobial resistance (AMR) to be a major threat to healthcare. From all available strategies, antimicrobial metals and, more specifically, silver showcase large bactericidal spectrum and limited toxic effect which coupled with a large range of processes available for their delivery made these materials as a clear candidate to tackle AMR. Previous reports have shown the ability of this metal to enact a synergistic effect with other antimicrobial therapies, nevertheless, the discovery of Ag resistance mechanisms since the early 70s and limited knowledge on the long term influence of silver on AMR poses a threat to their applicability. The present study provides quantitative data on the influence of silver based therapies on AMR development for a panel of reference and clinical strains of major nosocomial pathogens, revealing that prolonged silver exposure may detrimentally impact sensitivity to antibiotics. Graphical abstract: Image, graphical abstract